(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Electrical maintenance is the process of keeping the electronics equipment connected with panels, or in any other electrical device. Electrical maintenance focuses on repairing, replacing and maintaining electrical equipment utilized on a big scale. Maintenance covers different tasks including testing, repairing and replacing of the electrical and electronics equipment in buildings controlled by industrial, corporate, private and government organizations. In this article talked about the electrical installation and maintenance of power systems, in which maintenance of transformer displayed and its reading sample value of the equipments also presented. In this paper research of maintenance and installation split into two sections including rural and urban, it is observed that temperature, weather and environment are different for various locations which affect the equipment life and their and rate of maintenance is varied with regard to place. The ability of electrical repair is extremely essential since that expertise will determine the life of equipment and plant. In this document also displays the kinds of equipments needed during the maintenance and installation. Maintenance and installation are fascinating study subjects which are helpful for engineers, every equipment and gadget requires maintenance thus in this paper scope of maintenance given.